Vibration Response Analysis of a Tethered Unmanned Aerial Vehicle System under Transient Wind Field - Wei He; Suxia Zhang (International Journal of Aerospace Engineering)
The transient wind is one of the dangerous conditions encountered by tethered UAVs operating at the ocean, making the cable and the UAV generate complex nonlinear vibration responses threatening normal operation, even safe flight. There is a lack of research on the nonlinear vibration of the tethered UAV in a transient wind field environment. This study analyzes the vibration response of a tethered quadrotor UAV under a transient wind field, which helps to boost the tethered UAV applications, providing engineering suggestions to design these systems. Considering both cable and UAV motions, the coupled dynamic equations of the tethered UAV system are established based on the Hamilton principle. The variation law of the cable vibration amplitudes with wind field and position is analyzed through a one-minus-cosine gust profile to describe the transient wind field, which can evaluate the dynamic behavior of systems in the actual flight. Moreover, the positions of maximum vibration amplitude in tangential and normal directions are found to be approximately 9/10 and 9/20 from the lower end of the cable. Furthermore, the tethered UAV system vibrations are investigated under different structural parameters. The results indicate that the UAV can maintain a stable single-period motion by increasing the length or elastic modulus or selecting the appropriate diameters of the cable. Finally, an experiment is implemented on the vibration response of the tethered UAV system in a wind tunnel. The theoretical result is compatible with the experimental one, demonstrating the theoretical method’s accuracy.